Laboratory investigation of the recycled asphalt concrete with stable crumb rubber asphalt binder. (10th April 2019) - Ding, Xunhao; Chen, Luchuan; Ma, Tao; Ma, Haixia; Gu, Linhao; Chen, Tian; Ma, Yuan
Highlights: Performance of the recycled mixtures improved significantly by SCRA. Factors influencing the performance of recycled mixtures were revealed. Comprehensive recycling effect by the SCRA and rejuvenator were evaluated. Abstract: This paper summarizes an investigation of the performance of the recycled asphalt concrete with stable crumb rubber asphalt (SCRA) binder. Both the normal recycled asphalt mixtures and the SCRA recycled asphalt mixtures were prepared with the 0%, 30%, 50% content of the reclaimed asphalt pavement (RAP). Laboratory tests were carried out to compare the performance of different mixtures and the comprehensive recycling effect of the SCRA and rejuvenator were evaluated further. The performance evaluations included the dynamic stability (DS) by wheel-tracking test, failure strain by low-temperature bending beam test, Marshall strength ratio (MSR) by the immersion test and fatigue life by four-point bending beam test, which represented the high-, low-temperature performance, moisture stability and the fatigue resistance respectively. The testing results indicated that as the RAP content increased, the recycled asphalt mixtures showed a better high-temperature stability but a worse low-temperature property, moisture stability and fatigue life for both VA and SCRA recycled mixtures. The SCAR is much better than the virgin asphalt (VA) in recycling the aged asphalt mixtures with large RAP content which could reach 50%. The rejuvenator has a positive effect on the low-temperature performance, moisture stability and fatigue resistance. By the combining the use of the SCRA and rejuvenator, the low-temperature performance of the SCRA recycled asphalt mixtures could be improved further while the other performance retained a high level at the same time, which was enough for the engineering applications completely.